Monoaminergic control of spinal locomotor networks in SOD1G93A newborn mice - Milan, Léa; Barrière, Grégory; De Deurwaerdère, Philippe; Cazalets, Jean-René; Bertrand, Sandrine S. (Frontiers in Neural Circuits, 2014)
Mutations in the gene that encodes Cu/Zn-superoxide dismutase (SOD1) are the cause of approximately 20% of familial forms of amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease characterized by the progressive loss of motor neurons. While ALS symptoms appear in adulthood, spinal motoneurons exhibit functional alterations as early as the embryonic and postnatal stages in the murine model of ALS, the SOD1 mice. Monoaminergic - i.e., dopaminergic (DA), serotoninergic (5-HT) and noradrenergic (NA) - pathways powerfully control the spinal networks and contribute significantly to their embryonic and postnatal maturation. Alterations in monoaminergic neuromodulation during development could therefore lead to impairments in the motoneuronal physiology. In this study, we sought to determine whether the monoaminergic spinal systems are modified in the early stages of development in SOD1 mice. Using a post-mortem analysis by High Performance Liquid Chromatography (HPLC), the contents of monoaminergic neuromodulators and their metabolites were quantified in the lumbar spinal cord of SOD1 and wild-type (WT) mice aged one postnatal day (P1) and P10. This analysis underscores an increased content of DA in the SOD1 lumbar spinal cord compared to that of WT mice but failed to reveal any modification of the other monoaminergic contents. In a next step, we compared the efficiency of the monoaminergic compounds in triggering and modulating fictive locomotion in WT and SOD1 mice. This study was performed in P1-P3 SOD1 mice and age-matched control littermates using extracellular recordings from the lumbar ventral roots in the in vitro isolated spinal cord preparation. This analysis revealed that the spinal networks of SOD1G93A mice could generate normal locomotor activity in the presence of NMA-5-HT. Interestingly, we also observed that SOD1 spinal networks have an increased sensitivity to NA compared to WT spinal circuits but exhibited similar DA responses.